Dynamic modelling of bioconversion of domestic wastewater sludge for cellulase enzyme - Kabbashi, Nassereldeen Ahmed; Alam, Md. Zahangir; Abdul Rahim, Khadijah (Springer-Verlag Berlin Heidelberg, 2011)
A mathematical modeling of bioconversion of domestic wastewater sludge for cellulase enzyme production was constructed based on the ideal batch mode. The mathematical models was based on the mass balance equation and focused particularly on the biomass, substrate and product rate of reaction. The biomass, substrate and product considered in this project were glucosamine, reducing sugar and cellulase enzyme respectively. The optimal conditions of pH,temperature, inoculum size, substrate concentration, co-substrate concentration and agitation speed were maintained during the simulation. The MATLAB simulation has been done by using modified Monod equation and modified kinetic equations for biomass, substrate and product. The results showed that higher product yields would be achieved when optimal conditions of parameters were held constant, the time constraints was 10 days and 95% of confidence level had been achieved which determined the range of validity of k’s values for these models. This study also involved the quantitative analysis and qualitative analysis graphically for validation of models.